Outcomes of the International Seminar «Current Issues in Continuing Professional Education in Forensic Science» - Marina V. Toropova (Теория и практика судебной экспертизы, 2018)
The paper presents the outcomes of the International Interdepartmental Science and Practice Seminar «Current Issues in Continuing Professional Education in Forensic Science» hosted by the Russian Federal Centre of Forensic Science of the Russian Ministry of Justice in Moscow on May 22–23, 2018.